Kepuasan Hubungan Romantis pada Dewasa Awal yang Berpacaran - Shakira Jamil Achmawati Novel; I Gusti Ayu Diah Fridari (Badan Penerbit STIEPARI Press, 2025)
In a romantic relationship, satisfaction is one of the critical indicators of assessing the success of the relationship. This study aims to determine the factors influencing romantic relationship satisfaction among young adults in dating relationships. The method used is a literature review. Article sources were accessed through Google Scholar, Mendeley, and ProQuest literature databases with publication years between 2016 – 2023. The result of this study reveal factors influencing romantic relationship satisfaction among young adults in dating relationships. These factors are categorized into two groups, intrapersonal factors and interpersonal factors. Intrapersonal factors include romantic jealousy, personality, intimacy, commitment, passion, belief in love, and stress, while interpersonal factors include assertiveness, attachment style, conflict resolution style, physical attractiveness, and phubbing behavior.